Низкотемпературная модификация медных пленок под воздействием атомарного водорода - Zhavzharov, E. L.; Matyushin, V. M. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
The possibility of low-temperature modification of the properties of thin copper films under the influence of atomic hydrogen is considered. The results of an experimental study of changes in the adhesion and cohesion properties of copper films within the "copper – silicon" heterostructure as a function of the treatment time with atomic hydrogen are presented. A model is proposed that qualitatively explains the experimental results.